Culture and its Consequences for Entrepreneurship - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2002)
This special issue of the Journal "Entrepreneurship Theory and Practice" focuses on the relationship between culture and entrepreneurship. It adopts a broad definition of both culture and entrepreneurship. Culture is used to refer to the enduring set of values of a nation, a region, or an organization. Entrepreneurship is defined as the act and process by which societies, regions, organizations, or individuals identify and pursue business opportunities to create wealth. The articles in this special issue highlight opportunities for future research, both theoretical and empirical. These studies offer a preliminary roadmap for conducting influential and insightful research that can enrich your understanding of the interplay between culture and entrepreneurship. The author believes that this special issue provides the momentum for future research that will more closely address the relationship between manifestations of culture and forms of entrepreneurship. Numerous opportunities abound for behavioral research in the nexus of culture and entrepreneurship. Substantial gaps in our knowledge of this relationship and its contingencies need to be addressed in future research.